2004
DOI: 10.1161/01.cir.0000130848.18636.b2
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Cadmium, Smoking, and Increased Risk of Peripheral Arterial Disease

Abstract: Background— Lead and cadmium exposure may promote atherosclerosis, although the cardiovascular effects of chronic low-dose exposure are largely unknown. The objective of the present study was to evaluate the association between blood levels of lead and cadmium and peripheral arterial disease. Methods and Results— We analyzed data from 2125 participants who were ≥40 years of age in the 1999 to 2000 National Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
247
4
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(278 citation statements)
references
References 35 publications
14
247
4
8
Order By: Relevance
“…In NHANES 1999-2000 that examines more than 2000 people, blood Pb and blood Cd were found higher in smokers than in non-smokers. Pb was higher in men than in women and Cd was higher in women than in men in the same survey [26,28].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In NHANES 1999-2000 that examines more than 2000 people, blood Pb and blood Cd were found higher in smokers than in non-smokers. Pb was higher in men than in women and Cd was higher in women than in men in the same survey [26,28].…”
Section: Discussionmentioning
confidence: 89%
“…Meta-analyses of more than 60 researches show strong relationship between systolic and diastolic blood pressure and elevated blood Pb level [22][23][24]. High blood Pb level also correlates cardiovascular mortality and prevalence of peripheral arterial diseases [25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NHANES data linked Cd with cardiovascular outcomes and peripheral arterial disease. Navas-Acien et al (2004 reported that peripheral arterial disease might be associated with blood and urinary Cd, thus suggesting that Cd is involved in arterial dysfunction. The authors used the anklebrachial index to reflect peripheral arterial disease.…”
Section: Blood Pressure and Effects On Arteriesmentioning
confidence: 99%
“…62 In the NHANES cohort, cadmium exposure partially mediated the effect of smoking on peripheral arterial disease. 63 The relationship between cadmium exposure and matrix metalloproteinase activity in the vasculature is unexplored.…”
Section: Matrix Metalloproteinases and Vascular Pathophysiology: Focumentioning
confidence: 99%